2011
DOI: 10.1097/icu.0b013e328349419d
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial disorders and the eye

Abstract: Purpose of Review Mitochondrial disease is a heterogeneous group of energy metabolism disorders that present across all ages with a wide range of ocular or multi-systemic manifestations. This review focuses on recent progress made toward understanding the various ophthalmologic manifestations of primary mitochondrial diseases and discusses the implications of mitochondrial dysfunction, placing particular emphasis on recent investigations into the pathogenesis and emerging therapies for mitochondrial-based opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 41 publications
3
58
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]33,34,39 In this study, we partially elucidated the molecular mechanisms of cell apoptosis in diabetes-induced rats and demonstrated that curcumin was excellent for treatment. We found that neuronal loss occurred in the retinas of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]33,34,39 In this study, we partially elucidated the molecular mechanisms of cell apoptosis in diabetes-induced rats and demonstrated that curcumin was excellent for treatment. We found that neuronal loss occurred in the retinas of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have not yet been able to elucidate the mechanisms by which curcumin prevents the progression of diabetic retinopathy. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Although many studies have reported that curcumin rescues retinal neuronal cell cultures from glutamate toxicity, 36,37 researchers have not been able to determine how curcumin treatment ameliorates the diabetes-induced damage to retinal Department of Ophthalmology, Lishui Central Hospital and Fifth Affiliated Hospital of Wenzhou Medical University, Lishui, Zhejiang Province, People's Republic of China. *These two authors contributed equally to the work and therefore should be considered equivalent authors.…”
mentioning
confidence: 99%
“…Ophthalmological findings in different genetically verified MIDs have previously been reported by our multidisciplinary team (Gronlund et al 2010). Ophthalmological findings in Leigh syndrome are ptosis, nystagmus, strabismus, reduced visual acuity, retinal pigmentation/dystrophy and optic atrophy (Rose et al 2008;Gronlund et al 2010;Schrier & Falk 2011;Han et al 2015). In addition, non-specific corneal abnormalities and epithelial dysfunction of the ciliary body have been reported (Hayashi et al 2000;Tyni et al 2004).…”
mentioning
confidence: 95%
“…Ocular dysfunction is a common manifestation of mitochondrial disorders [58,59]. Both retinitis pigmentosa (RP) [58][59][60][61] and optic atrophy (OA) [58][59][60] are features of several well-documented mitochondrial genotypes.…”
Section: Eyesmentioning
confidence: 99%
“…Both retinitis pigmentosa (RP) [58][59][60][61] and optic atrophy (OA) [58][59][60] are features of several well-documented mitochondrial genotypes. RP is not uncommon in mtDNA point mutations and mtDNA depletion disorders.…”
Section: Eyesmentioning
confidence: 99%